Development Of Organic Rice Labels and Packaging in Cikurubuk Village to Improve Product Image: Pengembangan Label dan Kemasan Beras Organik di Desa Cikurubuk Untuk Meningkatkan Citra Produk - Bela Pertiwi, Annisa; Budiman, Budiman; Hadijah, Ijah; Rinaldi, Mario; Farid, Rudy; Firdaus Benyamin, Muhammad (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Consumers who care about health and the environment are increasingly liking food products such as organic rice. Product image that can be influenced by label and packaging design is one of the factors that can affect consumers. The purpose of this study is to find out the most effective label and packaging design elements to attract consumers' attention to organic rice in Cikurubuk Village, to find out the influence of label and packaging design on the image of organic rice products from Cikurubuk Village in the eyes of consumers, and to find out that the design of organic rice labels and packaging can increase buying interest and product competitiveness in the local and regional markets. The results show that label and packaging designs that emphasize natural quality, health, and sustainability can improve the image of the product and encourage consumers to buy the product. It is hoped that this research will help organic rice producers develop better marketing strategies through label and packaging design.